Telocytes of the male urogenital system: Interrelationships, possible functions, and pathological implications - Sanches, Bruno Domingos Azevedo; Tamarindo, Guilherme Henrique; Maldarine, Juliana Dos Santos; Da Silva, Alana Della Torre [UNESP]; Dos Santos, Vitória Alário [UNESP]; Góes, Rejane Maira [UNESP]; Taboga, Sebastião Roberto [UNESP]; Carvalho, Hernandes F. (Wiley, 2021)
The male urogenital system is composed of the reproductive system and the urinary tract; they have an interconnected embryonic development and share one of their anatomical components, the urethra. This system has a highly complex physiology deeply interconnected with the circulatory and nervous systems, as well as being capable of adapting to environmental variations; it also undergoes changes with aging and, in the case of the reproductive system, with seasonality. The stroma is an essential component in this physiological plasticity and its complexity has increased with the description in the last decade of a new cell type, the telocyte. Several studies have demonstrated the presence of telocytes in the organs of the male urogenital system and other systems; however, their exact function is not yet known. The present review addresses current knowledge about telocytes in the urogenital system in terms of their locations, interrelationships, possible functions and pathological implications. It has been found that telocytes in the urogenital system possibly have a leading role in stromal tissue organization/maintenance, in addition to participation in stem cell niches and an association with the immune system, as well as specific functions in the urogenital system, lipid synthesis in the testes, erythropoiesis in the kidneys and the micturition reflex in the bladder. There is also evidence that telocytes are involved in pathologies in the kidneys, urethra, bladder, prostate, and testes.
Keywords: CD90; fibroblast-like; male reproductive system; prostate; slow waves; smooth muscle cell; telocytes; tissue organization; urinary system